Isolation and characterization of Chromobacterium sp. fromlake water at Manipal International University - Sandrasaigaran, Pratheep; Rajandrai, Pavitraa; Mak, Woei Loon; Hasan, Hanan (Universiti Putra Malaysia, 2021)
Introduction: The violet-pigmented Chromobacterium spp. are vastly located in soil and surface water of subtropical regions. Majority of the species have been identified as highly potential in bio-industries; however, the bacterial pathogenicity is largely understudied. These bacteria are resistant to multiple-drugs and infections may cause sepsis and liver abscissions. Thus, this study aimed to characterize the violet-pigmented bacteria isolated from the lake in Manipal International University and further examine its antibiotic susceptibility. Methods: The isolated violet bacteria (Dyh27s2016) were subjected to the morphology, physiology, biochemical and antibiotic susceptibility tests. Also, the species were scrutinized via the 16S rRNA and phylogenetic analysis. In addition, the lake water physicochemical properties were examined to understand the bacterial adaptability in this region. Results: Dyh27s2016 strain was found to exhibit similar morphology and physiology characteristics to Chromobacterium spp. and be closely related to Chromobacterium amazonense (98% sequence-homology). However, the biochemical analysis indicated that this strain was capable of indole production; contrarily, Chromobacterium spp. were found mostly indole negative. On top of that, this strain also tested resistant to most β-lactam and aminoglycoside antibiotics. The adaptability of the Dyh27s2016 strain in this region might be supported by the satisfactory physiochemical properties of the lake water and mainly by the low dissolve oxygen concentration. Conclusion: The morphology, physiology, biochemical and molecular characterizations of Dyh27s2016 isolate show high similarity to Chromobacterium spp. and the multi-drug resistance of this strain can potentially harbour a threat to public health if contacted by humans or animals via food or water.